Method for synthesizing dendritic phenolic antioxidant - YANG HONGJUN; WANG JUN; ZHANG HUIPING; LI CUIQIN; LI JIE; DI XIAOHE; LV CHUNSHENG; GUO YANDONG (2010)
The invention relates to a method for synthesizing a dendritic phenolic antioxidant, which comprises the following steps: firstly, using ethylenediamine and methyl acrylate as raw materials; secondly, synthesizing frameworks of 0.5 generation polyamide-amine and 1.0 generation polyamide-amine through two steps including Michael addition reaction and amidation condensation reaction; thirdly, using the 1.0 generation polyamide-amine and beta-(3,5-di-tertiary-butyl-4-hydroxyphenyl) propionyl chloride as raw materials, and using triethylamine as an acid-binding agent and trichloromethane as a solvent to perform the amidation condensation reaction; and finally, performing reduced pressure distillation, extraction and filtering to obtain the dendritic phenolic antioxidant. The dendritic phenolic antioxidant has readily available reaction raw materials, mild reaction conditions, easy product purification and high product yield; and the reactions belongs to basic reaction types, so the dendritic phenolic antioxidant